Citizen speeches about death in conditions of dignity and about the potential application of accompanying measures in this process (Metropolitan Region, Chile) - Tassara, Gonzalo; Valenzuela, Catalina; Aravena, Luis; Sánchez, Úrsula; Sandoval, Hernán (Acta Bioethica, 2020)
This article presents the results of empirical research that investigates the citizen's perspectives regarding the issue of death with dignity and the legitimacy of the implementation of measures to accompany this process. Through the implementation and analysis of seven discussion groups, carried out in the Metropolitan Region of Santiago de Chile, it can be concluded that there are high levels of consensus among the citizens supporting the need for implementation of external measures to end the life of patients who request it due to suffering related to terminal illnesses, and the need to have legal regulations that supports its application. All of this has been evaluated within the framework of a broad citizen assessment of personal autonomy and from the narration of experiences that reveal the great emotional and monetary burden involved in the process of caring for people with terminal illnesses.